Description of a new Tiporus Watts, 1985 from northern Queensland, Australia (Coleoptera: Dytiscidae, Hydroporinae) - Hendrich, Lars; Balke, Michael; Watts, Chris H.s. (Zootaxa, 2016)
Tiporus queenslandicus sp. n. is described from NE Queensland. The new species is similar to T. undecimmaculatus (Clark, 1862) and T. giuliani (Watts, 1978) from the Northern Territory and north-western Australia but well characterized by its larger size, more elongate habitus, and form of median lobe and parameres. Tiporus queenslandicus sp. n. is a lotic species being collected from rest pools of intermittent creeks and rivers with a sandy bottom. Important species-defining characters (habitus, median lobe, paramere, protibia of male) are illustrated. Together with T. queenslandicus sp. n. the genus comprises now 13 species.